Acknowledgment to Reviewers of Behavioral Sciences in 2020 - Behavioral Sciences Editorial Office (Behavioral Sciences, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that Behavioral Sciences maintains its standards for the high quality of its published papers [...]